Attitude a guide to advanced flying training and tests - Hugh, John (Airlife, 1994)
Aimed at those involved in advanced flying training, this book is not a technical training manual but gives advice on choice of flying school, the likely costs and how long it will take. There is guidance on the various advanced flying tests, what the tests will comprise, what the examiners will be like, what they will be looking for, what the chances of a pass will be and what to do if you fail.